(untitled) (Research, Society and Development, 2025)
This study aims to analyze the impact of domestic violence on women’s physical and emotional health and understand the role of nurses in identifying, intervening, and supporting these victims. Through an integrative literature review, articles published between 2006 and 2025 in databases such as SciELO, LILACS, BDENF, PubMed, and Google Scholar were analyzed. The results reveal that domestic violence represents a serious public health problem, with significant physical and psychological consequences for victims. The nursing team, as the first point of contact in care, plays an essential role in recognizing signs of violence, actively listening, and appropriately referring women. However, a lack of technical and emotional preparation was found among professionals to deal with these cases, reinforcing the need for ongoing training, humanization of care, and the implementation of forensic nursing in the Brazilian context. It is concluded that the qualification and involvement of nurses are fundamental to addressing domestic violence and promoting women’s comprehensive health.